ANALISIS PREDIKSI KEBANGKRUTAN MODEL ALTMAN Z-SCORE DALAM UPAYA PENILAIAN KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX PERIODE 2010 â 2014 - Hermawan, Riana Agustiana; Kusuma, Indra Cahya (JURNAL AKUNIDA, 2016)
Jakarta Islamic Index the period of 2010-2014. By using Altman Z-Score model, counting each of distress prediction at every mining company that number 7. Analysis of tecnique in use is Altman Z-Score Model by formula Z = 1,2X1 + 1,4X2 + 3,3X3 + 0,6X4 + 1,0X5. Assessment criteria of Z > 2,99 categorized as health company, 1,81 < Z < 2,99 categorized as company in grey area or prone bangkrupt, and Z < 1,81 categorized as bangkrupt company. During research period showed that research in years 2010 has 100% or all of company sample in health condition, in years 2011 has 6 companies on health condition dan has 1 company on grey area condition. Meanwhile in 2012 years, has 5 companies on health condition dan 2 companies on grey area condition. In years 2013 has 5 companies on health condition, 1 company on grey area condition and 1 company on bangkrupt condition. In years 2014 has 5 companies on health condition, 1 company on grey area condition and 1 company on bangkrupt condition.Keywords : Altman Z-Score, Distress Prediction